Poverty Alleviation through Poultry Rearing-insights from Participatory Action Research of Farmer FIRST Project - Hari, R.; Prajapati, P.; Vishwakarma, R.; Upadhyay, D.; Singh, R.; Singh, S. R. K. (International Journal of Bio-resource and Stress Management, 2026)
The study was conducted during August, 2017–March, 2022 at Jabalpur, Madhya Pradesh, India under the ICAR sponsored Farmer FIRST project of NDVSU for the empowerment of smallholder farmers through poultry rearing. About 165 women farmer beneficiaries were selected for the poultry intervention through participatory action research method and they were given 20 Narmada Nidhi female and 2 male birds as part of improving their livelihood. Capacity building activities were also included along with input distributed. The results indicated that the productivity increased from 42 eggs household-1 to 103 eggs and the income from poultry rearing increased from Rs. 1856 from the start of project to Rs. 16931 during the financial year 2020–21. The contribution of poultry to livelihood increased from 15.67 in the year 2017–18 to 20.32% during 2020–21. The results showed that poultry helped in increasing the economic conditions of beneficiaries. The income obtained was primarily used for the meeting child care and household activities and very less was invested in sustaining the enterprise. Poultry farming had proved to be an important source of livelihood for rural women. With proper training and support, it enabled them to earn a steady income while taking care of responsibilities at home. The success of this initiative demonstrated the potential of small poultry units to uplift rural economies.